Surgical Removal of a Focal Fibrous Hyperplasia: Two Case Reports - Yousra, Zemmouri; Saliha, Chbicheb (International Journal of Innovative Research in Medical Science, 2021)
Focal fibrous hyperplasia is the most common epithelial benign tumor of the oral cavity. It is a localized reactive progressive, proliferation of oral mucosa in response to injury or local irritation. Females are twice more likely to develop fibroma than male. Surgical excision is performed and histological examination of the excised specimen and definitive diagnosis was obtained. This paper reports two cases of focal fibrous hyperplasia in both maxillary and mandibular locations.